PTU-190 Dissociation of upper limb temperature sensation in functional gastrointestinal disorders compared to blood relatives and unrelated controls. (22nd June 2015) - Etherson, KJ; Emmett, C; Syme, P; Yiannakou, Y
Abstract : Introduction: Temperature sensations from the upper limbs are transmitted through the contralateral spinothalamic tract in the cord to the ventral posterior lateral nucleus of the thalamus and then the primary somatic sensory cortex. Autonomic dysfunction arising in the central nervous system is known to affect the sympathetic function of skin which can result in a unilateral dissociation of temperature sensation. Autonomic dysfunction is also increasingly being hypothesised as a component of the functional gastrointestinal disorders (FGIDs). Aims: To assess the bilateral upper limb temperature sensation of a consecutive cohort of FGID patients and compare the incidence of temperature dissociation with controls. Method: Clinic attenders with a FGID diagnosis were sequentially invited to undertake the temperature sensation test. This comprised holding a bag of ice in both hands for 5 s and stating if they perceived the temperature to be either unilaterally colder or bilaterally equally cold. Unilaterally colder was considered to be evidence of upper limb temperature sensory dissociation. If a relative, spouse or friend was present they were also invited to participate as either a blood relative or un-related control. Results: 58 FGID patients and 58 controls undertook the temperature sensation test. 42 patients (72.4%) had upper limb temperature dissociation compared with 20 controls (34.4%) [P = 0.005]. 18/22 (81.8%) patients had dissociation compared to 8/22 (36.3%) blood relative controls [P = 0.049], and 24/36 (66.6%) patients had dissociation compared to 12/36 (33.3%) unrelated controls [P = 0.045]. There was no significant difference in the incidence of dissociation between blood relatives and unrelated controls, 36.3% and 33.3% respectively [P = 0.84]. Conclusion: Upper limb temperature dissociation seems to be more prevalent in patients with FGIDs than their blood relatives or unrelated controls. It may be associated with autonomic dysfunction as a result of a central nervous process. These findings are an interesting observation in our clinic, but do not constitute formal research and are limited by possible biases (selection and assessment) and a relatively small sample size. The observed proportions of temperature dissociation in these groups could be used to calculate an adequate sample size to detect whether this may be true in a formal research study of autonomic dysfunction in FGIDs. Disclosure of interest: None Declared.